Development of interactive media based on Google Sites for independent learning of extracurricular computer-aided design and drafting students - Efendi, Gus Farid Arya; Widiyanti; Tuwoso (Jurnal Inovasi Teknologi Pendidikan, 2026)
The implementation of Computer-Aided Design and Drafting (CADD) extracurricular training at Vocational High School Turen still relies on printed books and teacher demonstrations, which limit students' independence in learning and restrict the duration of practice. This development was carried out to help students learn independently, without time constraints, and to make it accessible from anywhere. This research is a development study using the ADDIE development model, which consists of five stages: 1.) Analyse; 2.) Design; 3.) Develop; 4.) Implement; 5.) Evaluate. The research and development process began with analysing student characteristics and needs, designing the concept, creating the product, validating it with subject matter experts and media experts, and testing the product using simple random sampling on three trial subjects participating in the CADD extracurricular activity at Vocational High School Turen, followed by evaluation based on improvement suggestions. The research instruments were based on media development theory, BNSP eligibility standards, and assessment standards set by the head of the standards, curriculum, and education assessment body. Based on expert media validation, the percentage was 88%, and expert material validation was 92%. The trial results yielded a 93% response rate from students regarding the developed product. The results of this research and development indicate that the interactive training media developed in Google Sites meet the criteria for suitability as training media. For future research, it is necessary to enhance the presentation and completeness of the material, as well as provide more complex exercises that keep pace with industry developments.